Reconciling past compromises: towards a more equitable future for Orang Asli in Malaysia - Al Hanisham Mohd Khalid,; Rohaida Nordin,; Safinaz Mohd. Hussein, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the wake of the COVID-19 pandemic, the present generation has more ability to shape the future than every previous generation in modern times. Intergenerational justice in general means meeting the current needs without jeopardising future generations; all generations are eligible to a healthy, balanced environment favourable to human progress and the State has fiduciary obligation to use and manage resources efficiently and further promotes balance and sound environmental policy. The synergy between its citizen and State create relationship known as “social contract”, but the word “social contract” has a very diverse and unique connotation in Malaysia. The “social contract” referred to the difficulties and intricate compromises reached between major ethnics in Malaysia regarding their mutual rights and privileges, since independence of Malaysia. The Aboriginal in Malaysia is also known as Orang Asli, their communities frequently associated with negative connotation and sometimes less fortunate when compared to other main ethnics in Malaysia. Over the time government regimes change guard but developments of reasonable policies and other actions that promotes intergenerational justice and sustainable development goal towards Orang Asli seem slow in progress. This paper aims to highlight the issues of plight among Orang Asli in Malaysia as they are the minorities within minority communities. In contrast to empirical research, doctrinal approach which is library-based focusing on reading and analysis of the primary and secondary materials will be applied throughout this study. It is the contention of this paper to promote better wellbeing of Orang Asli communities as part of Malaysia nation building.